The Characteristics of Mia Demsey’s Childhood Trauma in Jessie Ann Foley’s You Know I’m No Good - Yovita Olivia; Hariyono (Menulis: Jurnal Penelitian Nusantara, 2025)
Childhood trauma is a serious mental health issue with long-lasting effects on a child’s emotional and psychological well-being. This study analyses the characteristics of childhood trauma in Jessie Ann Foley’s You Know I’m No Good, focusing on Mia Dempsey, a teenager who struggles with traumatic experiences. This study employs a descriptive qualitative method, collecting primary data from the novel’s narrations and dialogues, and using Terr’s framework as secondary data to analyse the characteristics of childhood trauma. The findings show that Mia experiences repetitive behaviours, such as repeated engagement in unsafe sexual behaviour and substance use, as attempts to cope with her past sexual abuse. Her traumatic experiences also change her attitudes toward people, life, and the future, as she struggles to trust others, feels undeserving of a good life, and becomes pessimistic about her potential.